Integrasi Etnomatematika Dalam E-Comic Aritmatika Sosial, Eksplorasi Produk Budaya Makassar untuk Jenjang Sekolah Dasar - Annisa, Azizah Mujahidah; Wiradharma, Gunawan; Anam, Khaerul; Prasetyo, Mario Aditya (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research develops learning materials in the form of e-comics by utilizing ethnomathematics from Makassar culture, namely Jalangkote on social arithmetic material at the elementary school level with a self-paced instruction model. This research aims to explore how local cultural narratives can enrich mathematics content observing the feasibility and attractiveness of learning media. The research method employs the ADDIE Model, which is a three-stage process that encompasses design, development, and evaluation, for Research and Development (R&D). The development stage of this research is comprised of three phases, namely: (1) designing initial products (design) in the form of making storyboards and designing image designs for e-comic displays with Adobe premiere pro; (2) Development of initial products (development) in the form of validation evaluations by experts, which include the feasibility of material, media, and language, to ascertain the feasibility of the media being developed; and (3) perfecting initial products by making improvements to social arithmetic learning e-comics based on expert input. The results of this study have developed digital comics (e-comic) with an ethnomathematics approach on Social Arithmetic material for elementary school students declared valid according to expert standards. E-comic facilitates a more active learning experience with learning materials in an interesting and contextual environment. Keywords: e-comic, ethnomathematics, social arithmetic, learning media